Bacterial cell wall - Ghuysen, J. M.; Hakenbeck, R. (Regine), 1948- (New comprehensive biochemistry, 1994)
Studies of the bacterial cell wall emerged as a new field of research in the early 1950s, and has flourished in a multitude of directions. This excellent book provides an integrated collection of contributions forming a fundamental reference for researche.